A new species of Gripopterygidae (Insecta: Plecoptera) from Patagonia:Antarctoperla aonikenk sp. n. - S., Alejandro Vera (Zootaxa, 2023)
A new species of Gripopterygidae from Chilean Patagonia, Antarctoperla aonikenk sp. n., is described. This species shows wing dimorphism, with brachypterous males and macropterous females. The male genitalia have sufficient characters to diagnose and distinguish the new species from other species in the genus and from other Antarctoperlinae. Comparative illustrations are provided for the three species of the genus.